Climate emotions : stories of climate grief from the perspectives of the youth generation - Shen, Alice Lisi (Nanyang Technological University, 2021)
Climate Emotions is an illustrative, story-based publication aimed at youth from ages 6 to 12. It seeks to address the causes and implications of Climate Grief on youth individuals, and to visualize the emotional and psychological impact of climate change on mental health.